Low-temperature lithium-sulfur battery electrolyte and lithium-sulfur battery containing electrolyte

By using anionic acceptor additive with electron-deficient structure in the lithium sulfur battery electrolyte, the problem of capacity attenuation and poor performance of lithium sulfur batteries under low temperature and lean electrolyte conditions is solved, and the further development is achieved High sulfur utilization and battery performance.

CN119447464APending Publication Date: 2025-02-14PEKING UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411674444.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

Lithium-sulfur batteries have severe capacity decays and poor low-temperature performance in low-temperature environments. Especially under the conditions of lean electrolyte, the utilization rate and reversibility of sulfur are low, resulting in low energy density and short cycle life.

Method used

The interaction between anionic acceptor additives with electron-deficient structure and electron-rich sulfur is adopted to promote the dissolution of lithium polysulfide, prevent cluster formation, and improve reaction kinetics, thereby improving the battery's electrolyte-polyte and low-temperature conditions. Sulfur utilization rate.

Benefits of technology

The sulfur utilization rate of lithium-sulfur batteries under low temperature and electrolyte lean conditions is significantly improved, the circulation stability of the negative electrode is extended, and the energy density and cycle life of the battery are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119447464A_ABST
    Figure CN119447464A_ABST
Patent Text Reader

Abstract

The invention discloses a low-temperature lithium-sulfur battery electrolyte and a lithium-sulfur battery containing the electrolyte, and relates to the technical field of lithium-sulfur batteries. The electrolyte comprises a solvent, a lithium salt and an additive, the solvent is an ether solvent with a chain-shaped or cyclic molecular structure or a composite solvent composed of the ether solvent, preferably one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 1, 3-dioxolane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether; the additive is a borate or borane anion acceptor with an electron-deficient structure. According to the low-temperature lithium-sulfur battery electrolyte provided by the invention, an anion acceptor additive with an electron-deficient structure and electron-rich sulfur have relatively strong interaction, so that the dissolution of lithium polysulfide is promoted, the formation of lithium polysulfide clusters is prevented, and the reaction kinetics of the lithium polysulfide is promoted; and the sulfur utilization rate of the battery under a poor electrolyte condition and a low-temperature condition is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium-sulfur batteries, and in particular relates to a low-temperature lithium-sulfur battery electrolyte and a lithium-sulfur battery containing the electrolyte. Background Art

[0002] Sulfur has a high theoretical specific capacity and storage abundance. Lithium-sulfur batteries composed of lithium metal show high energy density and low cost, and have great application potential in energy storage, lightweight chemical power sources, such as drones, portable power sources, electric vehicles, and large-scale energy storage. However, the practical application of lithium-sulfur batteries is still restricted by their actual energy density. Especially under lean electrolyte conditions, the capacity of sulfur is restricted by the viscosity and kinetics of lithium polysulfide solutions, resulting in lower discharge capacity. In addition, its poor low-temperature properties also bring great challenges to its practical application, limiting its application in professional fields such as space exploration and seabed operations.

[0003] Currently, catalysts can be used to promote the conversion efficiency of the "liquid-solid" process and improve the low-temperature performance of lithium-sulfur batteries. However, its capacity under low-temperature conditions is still low, and most tests are still carried out under conditions of excess electrolyte, making it difficult to achieve a higher energy density. In poor electrolyte or low-temperature conditions, insufficient solvation of intermediate products and their cluster aggregation at high concentrations are the main factors limiting the sulfur capacity. Aggregated clusters of lithium polysulfide greatly hinder the solution-mediated reaction and significantly reduce the utilization and reversibility of sulfur. By regulating the electrolyte components: solvents, lithium salts and additives, the coordination structure and reaction activity of the intermediate lithium polysulfide can be effectively regulated.

[0004] CN202211587176.2 discloses a low-temperature resistant lithium-sulfur battery electrolyte. This patent introduces halogenated hydrocarbons into traditional electrolytes to solve the shortcomings of lithium-sulfur batteries in the prior art, such as severe capacity attenuation and poor low-temperature performance under low-temperature environments. The electron-withdrawing effect of the halogen atoms in halogenated hydrocarbons increases the electron-acquiring ability of the central atom, so that the additives are preferentially reduced and effectively passivate the electrode surface under higher potential conditions, forming a stable SE I film, reducing the charge transfer impedance, and increasing the diffusion rate of ions at low temperatures. In addition, since the halogenated hydrocarbon additive has a low freezing point, the introduction of the additive into the electrolyte greatly reduces the freezing point of the electrolyte, increases the solubility of the electrolyte at low temperatures, increases the low-temperature conductivity of the electrolyte, and improves the low-temperature performance of the lithium-sulfur battery.

[0005] At present, the above-mentioned lithium-sulfur battery electrolytes have improved the low-temperature performance of lithium-sulfur batteries by improving the freezing point and conductivity of the electrolyte and optimizing the electrode interface components, but the above-mentioned electrolytes still have problems such as short battery low-temperature cycle life and low energy density. Therefore, the development of efficient low-temperature lithium-sulfur battery electrolytes is of great significance for promoting the technological development of lithium-sulfur batteries and improving the energy density of battery lean electrolytes and low-temperature conditions. Summary of the invention

[0006] The object of the present invention is to provide a low-temperature lithium-sulfur battery electrolyte and a lithium-sulfur battery containing the electrolyte. A low-temperature lithium-sulfur battery electrolyte is proposed: an anion receptor additive with an electron-deficient structure has a strong interaction with electron-rich sulfur, promotes the dissolution of lithium polysulfide and prevents the formation of lithium polysulfide clusters, promotes the reaction kinetics of lithium polysulfide, and improves the sulfur utilization rate of the battery under poor electrolyte conditions and low temperature conditions, thereby solving the problems of short low-temperature cycle life of the battery and low energy density still existing in the existing electrolyte.

[0007] To achieve the above object, the present invention provides the following technical solutions:

[0008] A low-temperature lithium-sulfur battery electrolyte, comprising a solvent, a lithium salt and an additive; the solvent is an ether solvent having a chain or ring molecular structure or a composite solvent composed thereof, preferably one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 1,3-dioxolane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether and tetraethylene glycol dimethyl ether;

[0009] The lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(fluoromethylsulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate and lithium hexafluorophosphate;

[0010] The additive includes an anion receptor having an electron-deficient structure;

[0011] The electrolyte has a high solubility of lithium polysulfide and can effectively adjust the cluster structure of lithium polysulfide.

[0012] The present invention is further preferably characterized in that the volume mole fraction of the lithium salt is 0.4 to 3.0 mol / L.

[0013] The present invention is further preferably characterized in that: the additive further comprises lithium nitrate;

[0014] The mass fraction of the lithium nitrate is 0.5-12% of the total mass of the electrolyte;

[0015] Lithium nitrate can not only promote the three-dimensional deposition of lithium sulfide, but also form a stable interface film on the surface of the metal lithium negative electrode, thereby improving the cycle life of the battery; anion receptors usually contain electron-deficient sites, which are easy to form coordination structures with electron-rich sulfur, thereby regulating the morphology of lithium polysulfide, especially preventing the formation of lithium polysulfide clusters, thereby promoting the conversion of lithium polysulfide;

[0016] The anion receptor comprises one or more of tri(pentafluorophenyl)boron, triphenylboron, tetrafluorocatechol-pentafluorophenylborane, trimethyl borate, triethyl borate, triphenyl borate, tri(2,2,2-trifluoroethyl) borate, and tri(pentafluorophenyl) borate ester;

[0017] The mass fraction of the anion receptor is 0.05-5% of the total mass of the electrolyte;

[0018] The electrolyte can obtain a higher sulfur utilization rate under high sulfur loading or lean electrolyte or low temperature conditions, and the lithium negative electrode has a higher coulombic efficiency.

[0019] The present invention is further preferably provided that the present invention also includes a method for preparing a low-temperature lithium-sulfur battery electrolyte, wherein the low-temperature lithium-sulfur battery electrolyte is prepared by the following method:

[0020] (1) using molecular sieves to remove water from the solvent; standing for 48 to 72 hours;

[0021] (2) using a glass drying apparatus to dry the lithium salt in a vacuum at a high temperature to remove moisture, the temperature range is between 50 and 120 degrees Celsius, and the drying time is 24 hours;

[0022] (3) mixing the dried solvents to obtain a uniform solution;

[0023] (4) Adding the dried lithium salt and additives to the above-mentioned uniform solvent, the low-temperature lithium-sulfur battery electrolyte can be obtained.

[0024] A lithium-sulfur battery using a low-temperature lithium-sulfur battery electrolyte, the lithium-sulfur battery comprising a battery cell, the battery cell comprising a positive electrode, a separator, an electrolyte and a negative electrode.

[0025] The present invention is further preferably: the electrolyte is the electrolyte described above;

[0026] The positive electrode material is a sulfur-carbon composite material, wherein the carbon material includes but is not limited to Ketjen black, activated carbon, carbon nanotubes, graphene, carbon fiber, and the mass fraction of sulfur is 50-95%;

[0027] The negative electrode material includes lithium foil, lithium copper composite electrode, silicon carbon composite electrode, lithium indium composite electrode, graphite electrode and the like.

[0028] The present invention is further preferably: the positive electrode of the lithium-sulfur battery using the low-temperature lithium-sulfur battery electrolyte is prepared by the following method:

[0029] The positive electrode material, the conductive agent and the binder are dispersed in a solvent according to a certain mass ratio, mixed evenly, and then evenly coated on the aluminum current collector, and dried to obtain a positive electrode sheet;

[0030] The conductive agent includes but is not limited to one or more of super P, acetylene black, activated carbon, Ketjen black, and graphene carbon;

[0031] The binder includes polyvinylidene fluoride, polytetrafluoroethylene, LA133, sodium carboxymethyl cellulose or sodium alginate;

[0032] Select the dispersing solvent according to the type of binder. If polyvinylidene fluoride or polytetrafluoroethylene is used as the binder, use N-methylpyrrolidone as the dispersing liquid. If LA133, sodium carboxymethyl cellulose or sodium alginate is used as the binder, choose deionized water as the dispersing liquid.

[0033] The mass ratio of the positive electrode material, the conductive agent and the binder is 8:1:1 or 85:10:5.

[0034] The present invention is further preferably: the lithium-sulfur battery using the low-temperature lithium-sulfur battery electrolyte is prepared by the following method:

[0035] Assemble the positive electrode, separator, electrolyte, negative electrode and other accessories into the battery case in sequence and seal it with a sealing machine.

[0036] The present invention has the following beneficial effects:

[0037] 1. The present invention proposes a low-temperature lithium-sulfur battery electrolyte: an anion receptor additive with an electron-deficient structure has a strong interaction with electron-rich sulfur, which promotes the dissolution of lithium polysulfide and prevents the formation of lithium polysulfide clusters, promotes the reaction kinetics of lithium polysulfide, and improves the sulfur utilization rate of the battery under lean electrolyte conditions and low temperature conditions.

[0038] 2. The electrolyte proposed in the present invention has good lithium negative electrode cycle stability: the anion additive contains an electron-deficient structure and has good stability with lithium metal. In addition, the anion additive can regulate the coordination structure of the anion to further regulate the components of the negative electrode interface film and improve the lithium negative electrode cycle stability.

[0039] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.

[0041] Figure 1 The charge and discharge curves of the lithium-sulfur battery in Example 1 and Comparative Example 1 under the poor electrolyte condition of the present invention;

[0042] Figure 2 This is a cycle performance diagram of the lithium-sulfur battery under poor electrolyte conditions in Example 1 of the present invention;

[0043] Figure 3 This is a charge and discharge curve diagram of the lithium-sulfur battery in Example 2 of the present invention under poor electrolyte conditions;

[0044] Figure 4 This is a cycle performance diagram of the lithium-sulfur battery of Example 2 of the present invention;

[0045] Figure 5 The charge and discharge curves of the lithium-sulfur battery of Example 3 and Comparative Example 2 under low temperature conditions;

[0046] Figure 6 This is a cycle performance diagram of the lithium-sulfur battery of Example 3 of the present invention under low temperature conditions;

[0047] Figure 7 This is the charge and discharge curve of the lithium-sulfur battery of Example 4 of the present invention under low temperature conditions;

[0048] Figure 8 This is a cycle performance diagram of the lithium-sulfur battery of Example 4 of the present invention under low temperature conditions. DETAILED DESCRIPTION

[0049] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application may be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.

[0050] It should be noted that, unless otherwise specified, all technical and scientific terms used in this application have the same meanings as commonly understood by ordinary technicians in the technical field to which this application belongs. Specific embodiment 1

[0052] See also Figure 1-2The present invention is a low-temperature lithium-sulfur battery electrolyte, which includes a solvent, a lithium salt and an additive; the solvent is a mixed solvent composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio is 1:1; the lithium salt is lithium bis(trifluoromethylsulfonyl)imide, and the molar concentration in the electrolyte system is 0.8 mol / L; the additive is lithium nitrate and tris(pentafluorophenyl)boron, wherein the mass fraction of the lithium nitrate additive is 4%, and the mass fraction of the tris(pentafluorophenyl)boron additive is 1%.

[0053] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:

[0054] (1) adding a certain amount of molecular sieves into different solvents for dehydration treatment, and standing for 48-72 hours;

[0055] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.

[0056] (3) mixing the dried ethylene glycol dimethyl ether and 1,3-dioxolane in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane in the uniform solution is 50:50;

[0057] (4) adding the dried lithium salt and tris(pentafluorophenyl)borane additive to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte after standing for 24 hours (the concentration of lithium bis(trifluoromethylsulfonyl)imide is 0.8 mol / L, the mass fraction of lithium nitrate is 4%, and the mass fraction of tris(pentafluorophenyl)borane is 1%);

[0058] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.

[0059] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 5.5 mg / cm 2 , the electrolyte dosage is 4uL / mg s .

[0060] like Figure 1As shown, the electrolyte of this embodiment is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 5.5 mg / cm2 and an electrolyte dosage of 4.0 uL / mgs, the battery can release a specific capacity of up to 1201 mAh / g at a rate of 0.05C, showing that the electrolyte of this embodiment effectively improves the utilization rate of sulfur under lean electrolyte conditions. The electrolyte of Comparative Example 1 is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 5.5 mg / cm2 and an electrolyte dosage of 4.0 uL / mg, the battery can only obtain a specific capacity of 947 mAh / g at a rate of 0.05C, and a large polarization appears on the second discharge platform. The formation of lithium polysulfide clusters under lean electrolyte conditions reduces the reaction kinetics, which is not conducive to its continuous conversion;

[0061] like Figure 2 As shown, the electrolyte of this embodiment is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 5.5 mg / cm2 and an electrolyte dosage of 4.0 uL / mgs, the battery has a capacity retention rate of up to 83% after 100 cycles at a rate of 0.1C, demonstrating the good interface stability of the negative electrode of the electrolyte of Example 1 under lean electrolyte conditions. Specific embodiment 2

[0063] See also Figure 3-4 The present invention is a low-temperature lithium-sulfur battery electrolyte, which includes a solvent, a lithium salt and an additive; the solvent is a mixed solvent composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio is 1:1; the lithium salt is lithium bis(trifluoromethylsulfonyl)imide, and the molar concentration in the electrolyte system is 0.8 mol / L; the additive is lithium nitrate and tris(pentafluorophenyl)boron, wherein the mass fraction of the lithium nitrate additive is 4%, and the mass fraction of the tris(pentafluorophenyl)boron additive is 1%.

[0064] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:

[0065] (1) adding a certain amount of molecular sieves into different solvents for dehydration treatment, and standing for 48-72 hours;

[0066] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.

[0067] (3) mixing the dried ethylene glycol dimethyl ether and 1,3-dioxolane in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane in the uniform solution is 50:50;

[0068] (4) adding the dried lithium salt and tris(pentafluorophenyl)borane additive to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte after standing for 24 hours (the concentration of lithium bis(trifluoromethylsulfonyl)imide is 0.8 mol / L, the mass fraction of lithium nitrate is 4%, and the mass fraction of tris(pentafluorophenyl)borane is 1%);

[0069] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.

[0070] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 4.3 mg / cm 2 , the electrolyte dosage is 5uL / mg s .

[0071] like Figure 3 As shown, the electrolyte of this embodiment is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 4.3 mg / cm2 and an electrolyte dosage of 5.0 uL / mgs, the battery can release a specific capacity of up to 967 mAh / g at a rate of 0.1C, showing that the electrolyte of Example 2 effectively improves the utilization rate of sulfur under lean electrolyte conditions;

[0072] like Figure 4 As shown, the electrolyte of this embodiment is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 4.3 mg / cm2 and an electrolyte dosage of 5.0 uL / mgs, the battery has a capacity retention rate of up to 70.7% after 100 cycles at a rate of 0.1C, demonstrating the good interface stability of the negative electrode of the electrolyte of Example 2 under lean electrolyte conditions. Specific embodiment 3

[0074] See also Figure 5-6 The present invention is a low-temperature lithium-sulfur battery electrolyte, which includes a solvent, a lithium salt and an additive; the solvent is a mixed solvent composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio is 1:1; the lithium salt is lithium bis(trifluoromethylsulfonyl)imide, and the molar concentration in the electrolyte system is 0.8 mol / L; the additive is lithium nitrate and tris(pentafluorophenyl)boron, wherein the mass fraction of the lithium nitrate additive is 4%, and the mass fraction of the tris(pentafluorophenyl)boron additive is 0.5%.

[0075] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:

[0076] (1) adding a certain amount of molecular sieves into different solvents for dehydration treatment, and standing for 48-72 hours;

[0077] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.

[0078] (3) mixing the dried ethylene glycol dimethyl ether and 1,3-dioxolane in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane in the uniform solution is 50:50;

[0079] (4) adding the dried lithium salt and tris(pentafluorophenyl)borane additive to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte after standing for 24 hours (the concentration of lithium bis(trifluoromethylsulfonyl)imide is 0.8 mol / L, the mass fraction of lithium nitrate is 4%, and the mass fraction of tris(pentafluorophenyl)borane is 0.5%);

[0080] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.

[0081] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 1.1 mg / cm 2 , the electrolyte dosage is 20uL / mg s .

[0082] like Figure 5 As shown, the electrolyte of this embodiment is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 1.1 mg / cm2 and an electrolyte dosage of 20.0 uL / mgs, the battery can release a specific capacity of up to 1001 mAh / g at a rate of 0.1C at -25°C, demonstrating the faster lithium polysulfide reaction kinetics of the electrolyte of this example under low temperature conditions. The electrolyte of Comparative Example 2 is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 1.1 mg / cm2 and an electrolyte dosage of 20.0 uL / mgs, the battery can only release a specific capacity of 247 mAh / g at a rate of 0.1C at -25°C, and the second discharge platform disappears, indicating that the lithium polysulfide clusters severely slow down their reaction kinetics under low temperature conditions;

[0083] like Figure 6As shown, the electrolyte of this embodiment is used in a lithium-sulfur battery. Under the conditions of a sulfur loading of 1.1 mg / cm2 and an electrolyte dosage of 20.0 uL / mg, the battery has a capacity retention rate of 68% after 100 cycles at -25°C and a rate of 0.1C, demonstrating the good interface stability of the negative electrode of the electrolyte of Example 3 under lean electrolyte conditions. Specific embodiment 4

[0085] See also Figure 7-8 The present invention is a low-temperature lithium-sulfur battery electrolyte, which includes a solvent, a lithium salt and an additive; the solvent is a mixed solvent composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio is 1:1; the lithium salt is lithium bis(trifluoromethylsulfonyl)imide, and the molar concentration in the electrolyte system is 0.8 mol / L; the additive is lithium nitrate and tris(pentafluorophenyl)boron, wherein the mass fraction of the lithium nitrate additive is 4%, and the mass fraction of the tris(pentafluorophenyl)boron additive is 1%.

[0086] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:

[0087] (1) adding a certain amount of molecular sieves into different solvents for dehydration treatment, and standing for 48-72 hours;

[0088] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.

[0089] (3) mixing the dried ethylene glycol dimethyl ether and 1,3-dioxolane in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane in the uniform solution is 50:50;

[0090] (4) adding the dried lithium salt and tris(pentafluorophenyl)borane additive to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte after standing for 24 hours (the concentration of lithium bis(trifluoromethylsulfonyl)imide is 0.8 mol / L, the mass fraction of lithium nitrate is 4%, and the mass fraction of tris(pentafluorophenyl)borane is 1%);

[0091] The above-mentioned lithium-sulfur battery electrolyte is used to assemble a soft-pack lithium-sulfur battery. The lithium-sulfur battery consists of an aluminum-plastic film and a battery cell. The battery cell includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator and lithium metal negative electrode are stacked in sequence and placed in the aluminum-plastic film, and the electrolyte is injected to seal. After standing for 24 hours, the lithium-sulfur battery is vacuum-sealed to obtain a lithium-sulfur battery.

[0092] The positive electrode composition of the above-mentioned lithium-sulfur battery is graphene sulfur-Super P-LA133, in which the mass ratio of each component is 85:10:5, and the single-sided sulfur loading is 4.0 mg / cm 2 , the electrolyte dosage is 4uL / mgs.

[0093] like Figure 7 As shown, the electrolyte of this embodiment is used in a soft-pack lithium-sulfur battery. Under the conditions of a single-sided sulfur loading of 4.0 mg / cm2 and an electrolyte dosage of 4.0 uL / mgs, the battery can obtain a capacity of 1.9 Ah at 0°C and a rate of 0.05C, showing that the electrolyte of Example 4 has a faster lithium polysulfide reaction kinetics under low temperature conditions;

[0094] like Figure 8 As shown, the electrolyte of this embodiment is used in a lithium-sulfur battery. Under the conditions of a single-sided sulfur loading of 4.0 mg / cm2 and an electrolyte dosage of 4.0 uL / mg, the battery can be stably cycled 45 times at 0°C and a rate of 0.05C while maintaining a high coulombic efficiency, demonstrating the good interface stability of the electrolyte of Example 4 under lean electrolyte conditions.

[0095] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0096] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

[0097] Comparative Example 1

[0098] See also Figure 1 In comparative example 1, the electrolyte includes a solvent, a lithium salt and an additive; the solvent is a mixed solvent composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio is 1:1; the lithium salt is lithium bis(trifluoromethylsulfonyl)imide, and the molar concentration in the electrolyte system is 0.8 mol / L; the additive is lithium nitrate, wherein the mass fraction of the lithium nitrate additive is 4%.

[0099] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:

[0100] (1) adding a certain amount of molecular sieves into different solvents for dehydration treatment, and standing for 48-72 hours;

[0101] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.

[0102] (3) mixing the dried ethylene glycol dimethyl ether and 1,3-dioxolane in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane in the uniform solution is 50:50;

[0103] (4) adding the dried lithium salt and lithium nitrate additive to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 0.8 mol / L, and the mass fraction of lithium nitrate is 4%) after standing for 24 hours;

[0104] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.

[0105] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 5.5 mg / cm 2 , the electrolyte dosage is 4uL / mg s .

[0106] Comparative Example 2

[0107] See also Figure 5 In comparative example 2, the electrolyte includes a solvent, a lithium salt and an additive; the solvent is a mixed solvent composed of ethylene glycol dimethyl ether and 1,3-dioxolane, and the volume ratio is 1:1; the lithium salt is lithium bis(trifluoromethylsulfonyl)imide, and the molar concentration in the electrolyte system is 0.8 mol / L; the additive is lithium nitrate, wherein the mass fraction of the lithium nitrate additive is 4%.

[0108] A method for preparing a lithium-sulfur battery electrolyte, wherein the lithium-sulfur battery electrolyte is prepared by the following method:

[0109] (1) adding a certain amount of molecular sieves into different solvents for dehydration treatment, and standing for 48-72 hours;

[0110] (2) using a glass drying apparatus to perform high-temperature vacuum drying on the lithium salt used to remove moisture from the lithium salt. The drying temperature can be adjusted according to the characteristics of different lithium salts. The vacuum drying temperature is controlled at 50-120° C. and the drying time is 24 h.

[0111] (3) mixing the dried ethylene glycol dimethyl ether and 1,3-dioxolane in a certain volume ratio to obtain a uniform solution, wherein the volume ratio of ethylene glycol dimethyl ether to 1,3-dioxolane in the uniform solution is 50:50;

[0112] (4) adding the dried lithium salt and lithium nitrate additive to the above-mentioned uniform solvent in a certain ratio, and obtaining a lithium-sulfur battery electrolyte (the concentration of lithium bistrifluoromethylsulfonyl imide is 0.8 mol / L, and the mass fraction of lithium nitrate is 4%) after standing for 24 hours;

[0113] A set of lithium-sulfur batteries is assembled using the above-mentioned lithium-sulfur battery electrolyte. The lithium-sulfur battery consists of a battery positive and negative electrode shell and a battery core. The battery core includes a positive electrode, a separator, an electrolyte and a negative electrode. The prepared positive electrode, separator, electrolyte, negative electrode, gasket and spring sheet are assembled into the battery shell in sequence, and the lithium-sulfur battery is obtained after sealing with a sealing machine.

[0114] The positive electrode composition of the lithium-sulfur battery is graphene sulfur-Super P-polyvinylidene fluoride, in which the mass ratio of each component is 8:1:1, and the sulfur loading is 1.1 mg / cm 2 , the electrolyte dosage is 20uL / mgs.

Claims

1. A low-temperature lithium-sulfur battery electrolyte, characterized in that: Including solvents, lithium salts and additives; The solvent is an ether solvent with a chain or ring molecular structure or a composite solvent composed of the ether solvent, preferably one or more of ethylene glycol dimethyl ether, ethylene glycol diethyl ether, 1,3-dioxolane, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, triethylene glycol dimethyl ether, and tetraethylene glycol dimethyl ether; The lithium salt is one or more of lithium bis(trifluoromethylsulfonyl)imide, lithium trifluoromethylsulfonate, lithium bis(fluoromethylsulfonyl)imide, lithium perchlorate, lithium tetrafluoroborate and lithium hexafluorophosphate; The additive includes an anion receptor having an electron-deficient structure.

2. A low-temperature lithium-sulfur battery electrolyte according to claim 1, characterized in that: The volume molar fraction of the lithium salt is 0.4 to 3.0 mol / L.

3. A low-temperature lithium-sulfur battery electrolyte according to claim 1, characterized in that: The additive also includes lithium nitrate; The mass fraction of the lithium nitrate is 0.5-12% of the total mass of the electrolyte; The anion receptor comprises one or more of tri(pentafluorophenyl)boron, triphenylboron, tetrafluorocatechol-pentafluorophenylborane, trimethyl borate, triethyl borate, triphenyl borate, tri(2,2,2-trifluoroethyl) borate, and tri(pentafluorophenyl) borate ester; The mass fraction of the anion receptor is 0.05-5% of the total mass of the electrolyte.

4. A method for preparing a low-temperature lithium-sulfur battery electrolyte according to claims 1-3, characterized in that: The low-temperature lithium-sulfur battery electrolyte is prepared by the following method: (1) using molecular sieves to remove water from the solvent; standing for 48 to 72 hours; (2) using a glass drying apparatus to dry the lithium salt in a vacuum at a high temperature to remove moisture, the temperature range is between 50 and 120 degrees Celsius, and the drying time is 24 hours; (3) mixing the dried solvents to obtain a uniform solution; (4) Adding the dried lithium salt and additives to the above-mentioned uniform solvent, the low-temperature lithium-sulfur battery electrolyte can be obtained.

5. A lithium-sulfur battery using a low-temperature lithium-sulfur battery electrolyte, characterized in that: The lithium-sulfur battery comprises a battery cell, and the battery cell comprises a positive electrode, a separator, an electrolyte and a negative electrode.

6. A lithium-sulfur battery using a low-temperature lithium-sulfur battery electrolyte according to claim 5, characterized in that: The electrolyte is the electrolyte in claims 1-3; The positive electrode material is a sulfur-carbon composite material, and the mass fraction of sulfur is 50-95%; The negative electrode material includes lithium foil, lithium copper composite electrode, silicon carbon composite electrode, lithium indium composite electrode, graphite electrode and the like.

7. A lithium-sulfur battery using a low-temperature lithium-sulfur battery electrolyte according to claim 6, characterized in that: The positive electrode of the lithium-sulfur battery using the low-temperature lithium-sulfur battery electrolyte is prepared by the following method: The positive electrode material, the conductive agent and the binder are dispersed in a solvent, mixed evenly, and then evenly coated on an aluminum current collector, and dried to obtain a positive electrode sheet; The conductive agent includes but is not limited to one or more of super P, acetylene black, activated carbon, Ketjen black, and graphene carbon material; The binder includes but is not limited to polyvinylidene fluoride, polytetrafluoroethylene, LA133, sodium carboxymethyl cellulose or sodium alginate; The mass ratio of the positive electrode material, the conductive agent and the binder is 8:1:1 or 85:10:

5.

8. A lithium-sulfur battery using a low-temperature lithium-sulfur battery electrolyte according to claim 7, characterized in that: The lithium-sulfur battery using a low-temperature lithium-sulfur battery electrolyte is prepared by the following method: Assemble the positive electrode, separator, electrolyte, negative electrode and other accessories into the battery case and seal it with a sealing machine.

Citation Information

Patent Citations

  • Lithium-sulfur battery electrolyte and low-temperature-resistant lithium-sulfur battery

    CN118173887A

  • Local high-concentration lithium metal battery electrolyte containing anion acceptor additive

    CN111276744A

  • Novel electrolyte for lithium-sulfur battery, and lithium-sulfur battery

    CN113675476A

  • Electrolyte for lithium-sulfur battery and preparation method

    CN116826177A

  • Temperature management system of battery pack unit for electronic car using cooling water

    KR1020200135615A